1991
DOI: 10.1080/17843286.1991.11718158
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Intravenous Essential Amino-Acids in Catabolic Patients on Chronic Maintenance Hemodialysis

Abstract: The effect on the clinical status of catabolic hemodialysis patients of I.V. essential amino-acids administered over 3 months at the end of each dialysis is assessed in an open clinical follow-up study of 10 patients; these patients showed a progressive deterioration of general condition and a progressive weight loss in the period before the start of the treatment. The study was undertaken in a hospital dialysis unit, with as main outcome measures body weight, hematocrit, a scoring index of general condition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The difference in survival was limited to patients who did not have diabetes mellitus. Several other studies have also observed improvement in various nutritional parameters like body weight or albumin when IDPN was prescribed (26–32).…”
Section: Parenteral Nutrition In Pewmentioning
confidence: 98%
“…The difference in survival was limited to patients who did not have diabetes mellitus. Several other studies have also observed improvement in various nutritional parameters like body weight or albumin when IDPN was prescribed (26–32).…”
Section: Parenteral Nutrition In Pewmentioning
confidence: 98%